Stock market capitalism welfare capitalism : - Dore, Ronald (Oxford University Press, 2000)
This book provides a good guide of change in economic behaviours of countries. Although it challenges the less financailly astute reader, it makes more sense upon each reading. It is well-documented. The authro explicitly shows a warmth for people's daily lives as the basis of econoic systems.' H-Japan